Quality Management Principles in the Management of Shipboard Discharges - Koljatić, Vjekoslav; Šegulja, Ivica; Miculinić, Rikard (Promet - Traffic&Transportation, 2006)
Environmental control of vessels is a management functionthat requires applied technology, training and diligentmanagement. Quality Management is a tool for developing environmentalprograms to control corporate environmental exposures.The management of environmental regulations, requirementsand concerns requires a systematic approach. QualityManagement (QM) embodies principles of policy delineation,operations accountability, documentation and review.These principles are all transferable to most aspects of shipmanagement. Properly implemented, they assign respective responsibilitiesfor both shore side and shipboard staff Both ISMand IS0-9000 Certification requirements embody the principlesof QM as requirements for certification. If, however, onelooks beyond the certification process, these principles makegood business sense. The benefits of QM are both economic aswell as assisting in corporate risk management. This paper willfocus on the risk management benefits as they apply of environmentalhealth programs in the marine environment includingports.